Comparative Analysis of Anti-Inflammatory Flavones in Chrysanthemum indicum Capitula Using Primary Cultured Rat Hepatocytes - Keita Minamisaka; Airi Fujii; Cheng Li; Yuto Nishidono; Saki Shirako; Teruhisa Kawamura; Yukinobu Ikeya; Mikio Nishizawa (Molecules)
The capitula of Chrysanthemum indicum Linné or C. morifolium Ramatuelle (Kikuka in Japanese) are included in several formulae of Kampo medicines (traditional Japanese medicines), such as Chotosan, which is used for headache and dizziness. Luteolin, the principal constituent of C. indicum, has antioxidant and anti-inflammatory activities. However, the effects of other flavonoids on this crude drug have not yet been thoroughly investigated. To evaluate and compare anti-inflammatory effects, we used primary cultured rat hepatocytes, which produce proinflammatory mediators, such as nitric oxide (NO) and proinflammatory cytokines, in response to interleukin (IL)-1β. Eight derivatives of 5,7-dihydroxyflavone were purified and identified in the ethyl acetate-soluble fraction of a C. indicum capitulum extract: luteolin (Compound 1), apigenin (2), diosmetin (3), 5,7-dihydroxy-3′,4′,5′-trimethoxyflavone (4), acacetin (5), eupatilin (6), jaceosidin (7), and 6-methoxytricin (8). Luteolin is the most abundant compound in this fraction. All compounds significantly suppressed NO production in hepatocytes, with apigenin and acacetin showing the greatest efficacy. The comparison of the IC50 values of the inhibition of NO production suggests that substitutions by hydroxyl and methoxy groups at the C-3′ and C-4′ positions of 5,7-dihydroxyflavone may be at least essential for the suppression of NO production. In hepatocytes, acacetin and luteolin decreased the levels of mRNAs encoding inducible nitric oxide synthase (iNOS), proinflammatory cytokines, including tumor necrosis factor, IL-6, and type 1 IL-1 receptor, which regulates inflammatory responses. Based on the comparison of the IC50 values and the content, luteolin, jaceosidin, and diosmetin may be responsible for the anti-inflammatory effects of C. indicum capitula.